Dementias show differential physiological responses to salient sounds - Fletcher, Phillip D.; Nicholas, Jennifer M.; Shakespeare, Timothy J.; Downey, Laura E.; Golden, Hannah L.; Agustus, Jennifer L.; Clark, Camilla N.; Mummery, Catherine J.; Schott, Jonathan M.; Crutch, Sebastian J.; Warren, Jason D. (Frontiers in Behavioral Neuroscience, 2015)
Abnormal responsiveness to salient sensory signals is often a prominent feature of dementia diseases, particularly the frontotemporal lobar degenerations, but has been little studied. Here we assessed processing of one important class of salient signals, looming sounds, in canonical dementia syndromes. We manipulated tones using intensity cues to create percepts of salient approaching (‘looming’) or less salient withdrawing sounds. Pupil dilatation responses and behavioural rating responses to these stimuli were compared in patients fulfilling consensus criteria for dementia syndromes (semantic dementia, n=10; behavioural variant frontotemporal dementia, n=16, progressive non-fluent aphasia, n=12; amnestic Alzheimer’s disease, n=10) and a cohort of 26 healthy age-matched individuals. Approaching sounds were rated as more salient than withdrawing sounds by healthy older individuals but this behavioural response to salience did not differentiate healthy individuals from patients with dementia syndromes. Pupil responses to approaching sounds were greater than responses to withdrawing sounds in healthy older individuals and in patients with semantic dementia: this differential pupil response was reduced in patients with progressive nonfluent aphasia and Alzheimer’s disease relative both to the healthy control and semantic dementia groups, and did not correlate with nonverbal auditory semantic function. Autonomic responses to auditory salience are differentially affected by dementias and may constitute a novel biomarker of these diseases.